2021
DOI: 10.3390/toxins13100698
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Potential Cytotoxic Role of Bacillus cytotoxicus Cytotoxin K-1

Abstract: The thermotolerant representative of the Bacillus cereus group, Bacillus cytotoxicus, reliably harbors the coding gene of cytotoxin K-1 (CytK-1). This protein is a highly cytotoxic variant of CytK toxin, initially recovered from a diarrheal foodborne outbreak that caused the death of three people. In recent years, the cytotoxicity of B. cytotoxicus has become controversial, with some strains displaying a high cytotoxicity while others show no cytotoxicity towards cell lines. In order to better circumscribe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…strains by treating human intestinal cells (Caco-2 cell line) with bacterial culture supernatants. The results showed that a broad range of cytotoxicity values could be observed, in line with the literature [54][55][56][57]. Bacillus paranthracis (14SBCL566) and B. cytotoxicus (14SBCL15) induced the highest levels of cytotoxicity, while the non-cytotoxic strains included one "environmental" Bt, a B. weihenstephanensis (species assumed to be of low virulence [58]) and three non-Bc Bacillus spp., including B. amyloliquefaciens, classified as a "Qualified presumption of safety" organism by the European Food Safety Authority (EFSA) [59].…”
Section: Discussionsupporting
confidence: 85%
“…strains by treating human intestinal cells (Caco-2 cell line) with bacterial culture supernatants. The results showed that a broad range of cytotoxicity values could be observed, in line with the literature [54][55][56][57]. Bacillus paranthracis (14SBCL566) and B. cytotoxicus (14SBCL15) induced the highest levels of cytotoxicity, while the non-cytotoxic strains included one "environmental" Bt, a B. weihenstephanensis (species assumed to be of low virulence [58]) and three non-Bc Bacillus spp., including B. amyloliquefaciens, classified as a "Qualified presumption of safety" organism by the European Food Safety Authority (EFSA) [59].…”
Section: Discussionsupporting
confidence: 85%
“…The protein encoded by this new reading frame has a high level of homology to LukDv, a pore-forming toxin protein described in S. pneumoniae . This protein can form pores in the membranes of eukaryotic cells, unbalancing the partial pressure inside the host cells, which results in cell lysis, release of the nutrients into the environment, and ultimately in the death of these cells 15 . The novel protein is encoded by a gene with a high homology to cytK , which suggests a possibility of horizontal transfer of this gene among various gram-positive microorganisms that are in a physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chromosomal fragments of at least 791 kb could be transferred between strains of B. thuringiensis sv. israelensis and chromosomal markers were successfully transferred by pXO16 between strains of B. cytotoxicus (Makart et al, 2018;Koné et al, 2021). pXO16 transfer and capture capacities were also evaluated under different ecological and food-related conditions, such as the midgut of dipteran larvae or milk and rice pudding (Thomas et al, 2001;Van der Auwera et al, 2007; see Sections "Conjugation under 'natural' environmental conditions" and "Conjugation in foodstuffs").…”
Section: Kinetics Of Transfer and Dna Capture Propertiesmentioning
confidence: 99%